Combination of triapine, olaparib, and cediranib suppresses progression of BRCA-wild type and PARP inhibitor-resistant epithelial ovarian cancer - Lin, Z. Ping; Zhu, Yong-Lian; Lo, Ying-Chun; Moscarelli, Jake; Xiong, Amy; Korayem, Yasmin; Huang, Pamela H.; Giri, Smith; LoRusso, Patricia; Ratner, Elena S. (PLOS ONE, 2018)
PARP inhibitors target BRCA mutations and defective homologous recombination repair (HRR) for the treatment of epithelial ovarian cancer (EOC). However, the treatment of HRR-proficient EOC with PARP inhibitors remains challenging. The objective of this study was to determine whether the combination of triapine (ribonucleotide reductase inhibitor), cediranib (vascular endothelial growth factor receptor tyrosine kinase inhibitor), and the PARP inhibitor olaparib synergized against BRCA wild-type and HRR-proficient EOC in xenograft mouse models. In addition, the mechanisms by which cediranib augmented the efficacy of triapine and olaparib were investigated. BRCA-wild type and PARP inhibitor-resistant EOC cell lines were implanted subcutaneously (s.c.) into nude mice or injected intraperitoneally (i.p.) into SCID-Beige mice. Mice were then treated i.p. with olaparib, cediranib, triapine, various double and triple combinations. The volume of s.c tumor in nude mice and the abdominal circumference of SCID-Beige mice were measured to evaluate the effectiveness of the treatment to delay tumor growth and prolong the survival time of mice. In both xenograft mouse models, the combination of triapine, olaparib and cediranib resulted in marked suppression of BRCA-wild type EOC growth and significant prolongation of the survival time of mice, with efficacy greater than any double combinations and single drugs. Furthermore, we identified that cediranib abrogated pro-survival and anti-apoptotic AKT signaling, thereby enhancing the efficacy of triapine and olaparib against BRCA-wild type EOC cells. Taken together, our results demonstrate a proof-of-principle approach and the combination regiment holds promise in treating BRCA-wild type and PARP inhibitor-resistant EOC.